Molecular Study of Parvovirus B19 Infection in Children with Acute Myeloid Leukemia - El-Khier, Noha Tharwat Abou (Asian Pac J Cancer Prev, 2018)
BACKGROUND: Parvovirus B19 is a common viral infection in children. Nearby evidences are present about its association with acute leukemia, especially acute lymphoblast leukemia. Nevertheless, scanty reports have discussed any role in acute myeloid leukemia (AML). PURPOSE: To evaluate the frequency of virological markers of B19 infection including its DNA along with specific immunoglobulins G (IgG) and M (IgM) among children with newly diagnosed AML. Besides, describing the clinical importance of Parvovirus B19 infection in those patients. PATIENTS AND METHODS: A case-control retrospective study was conducted on 48 children recently diagnosed with AML before and during chemotherapy induction and 60 healthy control. Specific serum IgM and IgG levels were determined by enzyme linked immunosorbant assay (ELISA) and DNA detection by polymerase chain reaction (PCR). RESULTS: Parvovirus DNA was detected in 20 patients with AML. IgM was found in sera of four patients and one case had positive DNA and IgG (5%). Patients with recent parvovirus B19 infection had a significantly reduced hemoglobin levels, RBCs counts, platelet counts, neutrophil counts and absolute lymphocytosis (p=0.01, p=0.0001, p=0.01, p=0.02, p=0.0003, respectively). There were no clinical findings with statistically significant association to recent infection. Half of the patients with AML had positive PCR and/or IgM for parvovirus B19. Among children with AML under chemotherapy, there were reduced hemoglobin levels (P=0.03), reduced platelet counts (P=0.0001) and absolute neutropenia (mean±SD, 1.200 ±1.00) in those with parvovirus B19 infection. More than half of patients with parvovirus B19 (72.2%) had positive PCR and/or IgM and 36.4% of them had positive IgG. CONCLUSION: This study highlights that parvovirus B19 is common in children with AML either at diagnosis or under chemotherapy. There are no clinical manifestations that can be used as markers for its presence, but hematological laboratory findings can provide evidence for infection in the presence of anemia and neutropenia. Detection of parvovirus B19 by combined molecular and serological markers is required in such patients for accurate diagnosis.